Lutzomyia longipalpis in Brazil: a complex or a single species? A mini-review - Bauzer, Luiz G. S. R. (2007)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Bioquímica e Biologia Molecular. Rio de Janeiro, RJ, Brasil.